The God of the cross is One: Engaging the theology of Bram van de Beek - Verster, Pieter (Verbum et ecclesia, 2023)
The Dutch theologian, Bram van de Beek, has a radical Christological emphasis in his theology. In this world, we see the cross of Jesus. Essentially, God is One . The Father is the Father of the Son Jesus Christ, and the Holy Spirit is the Spirit of Christ. The Holy Spirit works primarily in the church and is not a general spirit or a spirit of goodwill. By participating in Jesus’ death and resurrection, the believer receives salvation. Van de Beek is of the opinion that understanding evolution is necessary and that evil in this world should also be regarded in the light of the cross. He is open to criticism in the light of his position on God and the creation regarding the view that death and evil are present from the beginning. One must, however, accept his Christological stance and his view that God is One , as highly acceptable. Intradisciplinary and/or interdisciplinary implications: This article is largely in the field of systematic theology, but mission studies is also relevant in interdisciplinary interaction.